Development of a footcare education intervention delivered by community health workers to Type 2 diabetes patients - Okatiranti, Okatiranti (2024)
Background: Diabetes-related complications can be severe and costly, particularly diabetic foot problems, which can arise or be exacerbated by patients’ lack of awareness of proper footcare. Indonesia has the fifth highest diabetes incidence globally and is expected to have a diabetic population of 28.6 million by 2045. It is predicted there will be an inevitable rise in the occurrence of diabetic foot ulcers (DFUs) that can be anticipated and forestalled with proactive measures. One potential approach is to involve community health workers (CHWs) who can increase community awareness about diabetes prevention and promotion. Although there is evidence demonstrating the effectiveness of CHWs delivering footcare interventions (FCIs) as part of Diabetes Self-Management Education (DSME) programmes in high-resource countries, there is limited evidence on delivering such interventions in low-resource countries. Furthermore, there is a lack of detailed information on the core components of FCI delivered by CHWs from previous review.